Blockade of Rho-associated kinase prevents inhibition of axon regeneration of peripheral nerves induced by anti-ganglioside antibodies - Berardo, Andrés; Bacaglio, Cristian R.; Báez, Bárbara B.; Sambuelli, Rubén; Sheikh, Kazim A.; Lopez, Pablo H. H. (Chinese Association of Rehabilitation Medicine, 2024)
Neural Regeneration Research: Impact Factor 2022: 6.1